Modulation in surface properties by Ni doping in Na2Ti3O7: effect on dry reforming of methane - Ghodke, Seema R.; Devi, R. Nandini (ACS Applied Engineering Materials, 2025)
Dry reforming of CH4 using CO2 is considered as an excellent process for converting two greenhouse gases to platform chemicals. However, the challenge is severe coking as well as sintering and consequent deactivation in the absence of steam as in the more prevalent steam reforming. Here, we present a layered Ti-based oxide with appropriate basicity to facilitate CO2 adsorption and active metal Ni incorporated in the lattice sites to minimize sintering. Ni-doped Na2Ti3O7 was synthesized using the sol–gel method and subsequently characterized and screened in dry reforming of methane. Characterization results indicate the successful formation of the monoclinic phase of Na2Ti3O7. The variant Na2Ni0.2Ti2.8O7, which contains a higher concentration of Ni, exhibited improved reducibility and basicity, as determined through H2-TPR and CO2-TPD analysis. The presence of hydroxide, carbonate, and bicarbonate species was confirmed via X-ray photoelectron spectroscopy (XPS) and diffuse reflectance infrared Fourier transformation (DRIFT) studies, leading to increased conversion of CH4 and CO2 over extended periods with the Na2Ti2.8Ni0.2O7 catalyst. Basic Ti–OH groups replenished under reaction conditions may play a vital role in reducing coke formation in this catalyst. Post-reaction characterization revealed phase transformations in low Ni content catalysts, as evidenced by X-ray diffraction (XRD) and RAMAN analysis. Additionally, the suppression of coke formation and morphological changes were assessed through thermogravimetric analysis (TGA) and field emission scanning electron microscopy (FESEM) analyses in Na2Ti2.8Ni0.2O7 catalyst, respectively. The study highlighted the significant influence of elevated Ni concentrations on phase stability and conversion efficiency in the dry reforming of methane. This also evidences the importance of defects created by appropriate doping, which modulates the surface properties facilitating coke gasification.